Mary Philadelphia Merrifield: Color History as Expertise. (3rd April 2017) - Loske, Alexandra
Abstract : The aim of this article is to provide a brief overview and initial examination of some primary sources relating to British color researcher Mary Philadelphia Merrifield (1804–1889) that have not previously been considered. These are approximately 150 letters written by Merrifield to her husband, who had remained in England with some of their children, during her two research journeys to continental Europe between 1844 and 1846. By selecting a few representative letters and passages, this article will argue that knowledge, as well as financial and social circumstances, was instrumental in the development of the culture of connoisseurship both inside and outside the museum environment. One of the aims is to highlight how Merrifield negotiated access to libraries, archives and art galleries and how her expertise, acquired while working on her translation of Cennino Cennini's Il libro dell'arte and other previous projects, together with her family and her class, helped her on this research journey.